Therapeutic Effects of Asparagus officinalis Extract on Carrageenan-Induced Allergic Asthma in Swiss Albino Mice - Elnagar, Doaa M; Banaeem, Sarah A; AL-Qahtani, Wejdan S; Al- Qahtani, Norah M; Rady, Ahmed M; Ibrahim, Khalid E; Alqarni, Aisha H; Alshareef, Shaden A; Almalki, Samiah A; Alabdulhadi, Nuha M (Pharmaceutical Science: New Insights and Developments Vol. 3, 2025)
Background: Allergic asthma is a chronic inflammatory alteration of lung airways stimulated by immune-mediated reactions. The most represented symptoms of asthma are cough, chest tightness, shortness of breath and wheezing. Purpose: To determine the inhibitory effect of Asparagus officinalis extract (AOE) on allergic asthma induced by carrageenan (CGN). Methods: Forty male mice were divided into 4 groups: the 1st group was untreated control; the 2nd group was treated orally and daily with 500 mg/kg AOE for one week; the 3rd group was treated with a single dose of CGN 2 % w/v (200 µL/mice) intraperitoneally and left for one week; while the 4th group was treated first with CGN as in the 3rd group and treated with AOE as in the 2nd group after CGN injection for one week. After treatment, the animals were sacrificed, and blood samples were subjected to white blood cell count. IL-6 and TNF-\(α\) was measured in the lung homogenate while histopathological analysis was performed for lung samples. Results: A single dose of CGN resulted in a significant increase in white blood cell (WBC) count and pro-inflammatory cytokines IL-6 (490) and TNF-\(α\) (980) pg/ml; p = 0). Histopathological analysis showed severe lung alterations such as accumulation of infiltration cells that blocked alveolar sacs, and over-secretion of collagenous fibers, extracellular matrix, and hyaline membranes. Moreover, treatment with AOE after CGN injection significantly reduced WBC count (14x109) (p = 0) and pro-inflammatory cytokines (IL-6 (300) and TNF-\(α\) (830)pg/ml) that were raised by CGN (p = 0). Furthermore, AOE reduced the pathological signs that were induced by the matrix, and to the improvement of lung function and reduction of collagenous fibers and hyaline membranes. Conclusion: Carrageenan is an allergen-induced inflammatory agent and causes marked pathological alterations, thereby increasing pulmonary pathological scarring in addition to increasing the WBC count and pro-inflammatory cytokines. Asparagus officinalis extract reduces the allergic effect and lung pathological signs induced by CGN. Since AOE inhibits the production of inflammatory cytokines, it has the potential to be developed as a source of active pharmaceutical ingredients for the management of lung and airway injury.